Handbook of Fuel Cells 2010
DOI: 10.1002/9780470974001.f204033
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen evolution reaction

Abstract: This chapter presents a review of electrode materials used for the hydrogen evolution reactions and a comparison of their electrocatalytic activities. The introduction presents a brief definition of various thermodynamic water electrolysis potentials. In general, there are two ways to improve the performance of electrode materials: (1) use of electrode materials characterized by higher intrinsic activity i.e., higher exchange current density and (2) use of electrodes characterized by large real surface area. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
79
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(134 citation statements)
references
References 236 publications
9
79
0
4
Order By: Relevance
“…According to the literature of HER on transition metals [10,11,19] and the kinetic parameters obtained (Tafel slopes, b, ranging from 0.113 V dec -1 to 0.137 V dec -1 at 30 ºC, and cathodic transfer coefficient, α c , close to 0.5) we can conclude that the HER on the developed electrocatalysts takes place via the Volmer-Heyrovsky mechanism. Table 3 includes the overpotentials at a fixed current density of -100 mA cm -2 , Another good parameter to assess the catalytic activity is the apparent activation energy (E a ) at equilibrium potential [53].…”
Section: Polarization Measurementsmentioning
confidence: 66%
See 2 more Smart Citations
“…According to the literature of HER on transition metals [10,11,19] and the kinetic parameters obtained (Tafel slopes, b, ranging from 0.113 V dec -1 to 0.137 V dec -1 at 30 ºC, and cathodic transfer coefficient, α c , close to 0.5) we can conclude that the HER on the developed electrocatalysts takes place via the Volmer-Heyrovsky mechanism. Table 3 includes the overpotentials at a fixed current density of -100 mA cm -2 , Another good parameter to assess the catalytic activity is the apparent activation energy (E a ) at equilibrium potential [53].…”
Section: Polarization Measurementsmentioning
confidence: 66%
“…Platinum is the electrode material with the highest catalytic activity for HER. However, its high cost and scarcity are the two major barriers for its usage in the industrial water electrolysis, which requires searching for other cheaper and more available materials with good catalytic activity [4,9,10]. Ni-based materials have attracted more and more attention due to their good activity for HER and sufficient corrosion resistance in alkaline solutions at considerable low cost [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exhaustive reviews of RDE extracted parameters can be found in Refs. [24][25][26][27]. More specifically, on Pt, there was a general agreement that i 0 -values fall into the range of ≈1 mA/cm 2 Pt , [28][29][30] with anodic and cathodic Tafel slopes of 30 mV/decade.…”
mentioning
confidence: 67%
“…While going to higher overpotential, the hydrogen adsorption on the catalyst surface approaches saturation and the initial discharge step becomes the rate determining. [52] The Gibbs free energy for the absorption also depends on the rate determining step. [53,13] If DG H* is positive, the H-adsorption step will be the rate determining step, whereas, a negative value indicates the involvement of the H desorption step as the rate determining step.…”
Section: Resultsmentioning
confidence: 99%